Modelo de estratos por estimulabilidade e complexidade de segmentos: desenvolvimento e aplicação em software - Brancalioni, Ana Rita (2015)
The objective of this study was to develop a rehabilitation model called Strata Model Based on Stimulability and Segment Complexity, and perform the computer-assisted application of such proposal as a therapeutic resource in order to select target segments and stimulus words, predict generalizations and conduct activities for the treatment of phonological disorders. The Strata Model was based on the Segment Production Level (variable created to represent parameters for the assessment of the phonological system, the phonetic inventory and stimulability) and on the Complexity of Distinctive Features (Implicational Model of Feature Complexity - IMFC). The selection of stimulus words was based on environments that favored correct production, while the therapeutic activities were based on a mixed approach, wherein different models, procedures and strategies were combined, adapted and created. The Model has established four strata for treatment selection, and it has also predicted the generalizations that occur when a certain target segment is selected. Different programming patterns have been developed in order to: collect and store data on phonological assessments and stimulability; select the most favorable target segments; create therapeutic activities and strategies; aid the collection and storage of therapeutic data. All the developed programming patterns comprised the Speech Intervention Software (SIFALA). Four subjects with phonological disorders received speech therapy based on the Strata Model and the proposed intervention with SIFALA. A comparison was performed of data on phonetic inventory, phonological system and number of correctly produced consonants between the phonological assessment prior to therapy and the one after therapy. For data analysis, the Chi-square test was used at a significance level of 5% (p<0.05). The use of SIFALA to collect and store data on speech production assessments as well as select target segments and stimulus words, has proved very useful for the work of speech therapists. Moreover, all playful activities conducted during therapy motivated the subjects and fostered learning. All the subjects, who were treated by different strata, showed improvement, as evidenced by segments that were acquired in the phonetic inventory and established in the phonological system. In addition, there was a greater number of correctly produced consonants by all subjects after therapy, and the difference was statistically significant. The selection of target segments, based on the Model, promoted generalizations throughout the treatment, thus reducing the length of treatment required. All the programming patterns developed, which comprise the software SIFALA, are easy to apply and can be useful in clinical practice. They can also be an important tool to store the results of therapy. The results have corroborated theoretical evidence and confirmed the positive effect of the Strata Model and the proposed intervention with SIFALA for treatment of phonological disorders.